Exercise practice by individuals with diabetes mellitus (Research, Society and Development, 2020)
Diabetes mellitus (DM) is associated with a group of metabolic diseases characterized by chronic hyperglycemia, due to defects in insulin action or secretion. Non-pharmacological treatment plays a major role in DM improvement and control. This treatment encompasses a number of aspects such as: lifestyle change, eating habits and exercise. This study aimed to highlight through a literature review the benefits of physical exercise practice by individuals with diabetes mellitus. This is an integrative literature review, for its construction we used the following databases: Scielo, VHL and Google academic. It was found that the incentive for lifestyle changes, related to changes in eating habits, physical exercise, can prevent or delay diabetes mellitus, improving blood glucose control, metabolic complications, enabling a better quality of life. to individuals with diabetes mellitus.